Inhibitory Effect of Silver Nano Particles (AgNPs) Against Biofilm Formation in Multidrug Resistance P. aeruginosa Isolated from Burn infections - Huda H. Al-Hasnawy (Journal of Global Pharma Technology, 2017)
P. aeruginosa is an opportunistic pathogen that display uncommon phenomena of antimicrobial resistance. It is important to reminder that more than (80 %) of bacterial infections are caused by biofilms. Disruption and inhibition of preformed biofilms can be accomplished using silver nanoparticles. Out of 40, 22 (55%)  P. aeuroginosa isolates were recovered isolated pathogen was subjected to antibiotic susceptibility test using disc diffusion test. Screening of silver resistance using silver nitrate also done by agar dilution method using different concentrations (100µglml-400µglm). Formation of biofilm was detected. Silver nano particles were prepared and tested for anti-biofilm activity using different concentrations ranging from (2.5µg/ml-20µg/ml) employing tissue culture plate method. P. aeruginosa isolates were recovered from burn unit at a percent (55%), those isolates were found to be multidrug resistance and silver resistance as following: (100%) for each of piperacillin, imipenem and Cefotaxime. While (88%), (65%), (62%) for amikacin, ceftriaxone and gentamicin respectively. Biofilm production was detected quantitatively by microtiter plate method (100%), qualitatively via congo red agar method (44%) in multidrug resistant P. aeruginosa isolates. The inhibitory effect of silver nano particles in formation of biofilm was estimated using tissue culture plate method using different concentrations ranging from (2.5µg/ml -20µg/ml) and show high inhibition rate at 20µg/ml. This study concluded that silver nano particles have good antibiofilm activity with small concentration that could be used as an alternative therapy in those opportunistic pathogen.Keywords: Silvernanoparticles, P.aeruginosa, Biofilm Inhibition, Biofilm Formation.